Designing medical technology for resilience: integrating health economics and human factors approaches. (2nd January 2018) - Borsci, Simone; Uchegbu, Ijeoma; Buckle, Peter; Ni, Zhifang; Walne, Simon; Hanna, George B.
ABSTRACT: Introduction : The slow adoption of innovation into healthcare calls into question the manner of evidence generation for medical technology. This paper identifies potential reasons for this including a lack of attention to human factors, poor evaluation of economic benefits, lack of understanding of the existing healthcare system and a failure to recognise the need to generate resilient products. Areas covered : Recognising a cross-disciplinary need to enhance evidence generation early in a technology's life cycle, the present paper proposes a new approach that integrates human factors and health economic evaluation as part of a wider systems approach to the design of technology. This approach (Human and Economic Resilience Design for Medical Technology or HERD MedTech) supports early stages of product development and is based on the recent experiences of the National Institute for Health Research London Diagnostic Evidence Co-operative in the UK. Expert commentary : HERD MedTech i) proposes a shift from design for usability to design for resilience, ii) aspires to reduce the need for service adaptation to technological constraints iii) ensures value of innovation at the time of product development, and iv) aims to stimulate discussion around the integration of pre- and post-market methods of assessment of medical technology.